The Association of Fat-Mass-and Obesity-Associated Gene Polymorphism (rs9939609) With Colorectal Cancer: A Case-Control Study - Gholamalizadeh, Maryam; Akbari, Mohammad Esmail; Doaei, Saeid; Davoodi, Sayed Hossein; Bahar, Bojlul; Tabesh, Ghasem Azizi; Sadeghi, Hossein; Razavi Hashemi, Melika; Kheyrani, Elham; Rastgoo, Samira; Hajipour, Azadeh; Aslany, Zahra; et al. (Frontiers in Oncology, 2021)
Background and aim: The association between the rs9939609 polymorphism of fat mass- and obesity- associated gene and risk of colorectal cancer is controversial. This study aims to evaluate the relationship between FTO rs9939609 polymorphism and colorectal cancer (CRC) in Iranian people. Methods: A case-control study was conducted on 125 patients with CRC and 250 healthy subjects in Tehran, Iran. Demographic data and blood samples were collected from all participants. Genotyping of rs9939609 polymorphism was performed by the tetra-primer amplification refractory mutation system-polymerase chain reaction (T-ARMS-PCR) method. Results: The occurrence of AA genotype of FTO rs9939609 polymorphism in the colorectal cancer patients was significantly higher compared to that of healthy subjects (16.4% vs. 2.9%, respectively, P=0.02). The association between the frequency of risk allele of the FTO polymorphism and CRC (B=1.67, P=0.042) remained significant after adjustment for age. Further adjustment for gender (model 2) and marital status (model 3) did not change this result (B=1.67, P= 0.042 and B=1.67, P=0.043, respectively). The results remained significant after additional adjustment for ethnicity (B=1.57, P= 0.047). Conclusion: We found a positive association between the A allele of the rs9939609 polymorphism and CRC. Future studies are required to identify the underlying mechanisms.